Strategi Pengelolaan Dana Desa Untuk Meningkatkan Perekonomian Masyarakat Desa Bulu Tellue Kecamatan Bulupoddo Kabupaten Sinjai Dalam Perspektif Hukum Ekonomi Syariah - Al-Abrar, Muh.; Hasibuddin, M.; Lawang, Hasanna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the strategy of managing village funds in improving the economic welfare of the community in Bulutellue Village, Bulupoddo Sub-district, Sinjai Regency, and to analyze its implementation from the perspective of Islamic Economic Law. Village funds are an essential policy instrument provided by the central government to accelerate rural development and enhance community welfare. However, the success of village fund utilization largely depends on the strategies adopted, particularly in terms of planning, implementation, and evaluation. Therefore, it is crucial to assess how village authorities manage these funds effectively and in accordance with Islamic values. This research employs a descriptive qualitative approach, using data collection techniques such as direct observation, in-depth interviews, and documentation. The findings show that the village government of Bulutellue has implemented participatory and transparent management strategies, including village deliberations, the strengthening of Village-Owned Enterprises (BUMDes), infrastructure development, and the revitalization of the village market. These strategies have contributed significantly to improving the standard of living of the villagers by increasing income, expanding economic access, and providing adequate public facilities. from the research results, the management strategies employed in Bulutellue Village reflect the principles of justice, trust (amanah), public interest (maslahah), and transparency. There are no indications of riba (usury), gharar (uncertainty), or abuse of authority in the management process, and the funded programs tend to be productive and empowering. Thus, Sharia-based village fund management not only supports physical development but also strengthens the community's economic foundation in a sustainable and equitable manner.